Biomarker‐based development for optimized ACI‐24, a novel candidate vaccine for the treatment and prevention of Alzheimer's disease. (20th December 2022) - Sol, Olivier; Lê, Bénédicte; Valatsou, Elena; Delpretti, Saskia; Rongere, Julien; Vukicevic, Marija; Gray, Julian JG; Hliva, Valerie; Kosco‐Vilbois, Marie; Pfeifer, Andrea; Streffer, Johannes
Abstract: Background: Amyloid plaques and neurofibrillary tangles are the neuropathologic hallmarks of Alzheimer's disease (AD) with the key constituents being Amyloid Beta (Abeta) and Tau protein, respectively. However, the initiation and propagation of neurodegeneration and neurotoxicity in Alzheimer's disease remains incompletely understood despite recent important progress in clinical trials. It is apparent that small aggregates such as Abeta oligomers or fragments such as Abeta 1‐42 and pyroglutamate Abeta3‐42 (pGlu‐Abeta3‐42)) are of key importance for disease initiation with significant implications for translational medicine and success in clinical trial development. Method: ACI‐24 is a vaccine targeting Abeta for the treatment and prevention of AD. Initial clinical data have demonstrated safety and an initial pharmacodynamic response, both in sporadic AD and people with Down syndrome (DS), a specifically vulnerable population predisposed to developing AD. Preclinical data have recently demonstrated that a new, optimized formulation of ACI‐24 has significantly improved immunogenicity against key toxic species, i.e., Abeta oligomers, Abeta 1‐42 and pGlu‐Abeta3‐42. Recent clinical trial results in AD, specifically with monoclonal antibodies targeting Abeta, have successfully employed translational biomarkers, including Amyloid PET, as key decision markers and predictors of clinical benefit. Result: We present an innovative translational clinical trial design to understand the immunogenic properties of optimized ACI‐24 in sporadic AD and in people with DS. The biomarker‐based design, including multiple interim analyses, will enable (I) assessment of early safety and immunogenicity, (II) dose selection for early and meaningful readouts on translational biomarkers including Amyloid PET, (III) the safe transition into the more vulnerable DS population and (IV) informed transition into pivotal studies. Conclusion: The Alzheimer's disease field needs new treatments and clinical trial approaches. Vaccination is a proven approach to managing diseases affecting global populations. The field of biomarker‐based translational medicine has been mobilized by the recent understanding of how to clinically evaluate targeting of toxic Abeta fragments and aggregates in trials using monoclonal antibodies. Here, we demonstrate how we utilize these advances in an innovative clinical trial design for an efficient, evidence‐based translational medicine approach to test optimized ACI‐24 as a novel Abeta vaccine candidate.